A princess for Christmas [videorecording (DVD)] - Damian, Michael, 1962-; Damian, Janeen, 1961-; Krevoy, Brad; Moore, Roger, 1927-2017 (Lionsgate, 2012)
Jules Daly is the new guardian to her niece and nephew. On the day she loses her job and nanny, an invitation arrives to spend a royal Christmas in Europe with the children's grandfather, the Duke of Castlebury Hall. Once Jules and the children arrive at the castle, laughter soon fills the once quiet halls, giving everyone hope and joy for the season. And when Jules captures the heart of the dashing Prince Ashton, both of their lives change in unexpected ways!